Antimicrobial susceptibility of Staphylococcus aureus isolated from hospital inpatients, 2009: Report from the Australian Group on Antimicrobial Resistance - Nimmo, G.; Pearson, J.; Collignon, P.; Christiansen, K.; Coombs, Geoffrey; Bell, J.; McLaws, M.; Australian, G. (2011)
In 2009, the Australian Group on Antimicrobial Resistance (AGAR) conducted a period-prevalence survey of clinical Staphylococcus aureus isolated from hospital inpatients. Thirty medical microbiology laboratories from each state and mainland territory participated. Specimens were collected more than 48 hours post-admission. Isolates were tested by Vitek2 (AST-P579 card) and by Etest for daptomycin. Nationally, the proportion of S. aureus that were MRSA was 33.6%, ranging from 27.3% in South Australia to 41.4% in New South Wales/Australian Capital Territory. Resistance to the non-beta-lactam antimicrobials was common except for rifampicin, fusidic acid, daptomycin and high-level mupirocin. No resistance was detected for vancomycin, teicoplanin, quinupristin-dalfopristin or linezolid. Resistance in the methicillin susceptible S. aureus (MSSA) was rare apart from erythromycin (12%) and absent for vancomycin, teicoplanin, daptomycin, quinupristin-dalfopristin and linezolid. The proportion of methicillin resistant S. aureus (MRSA) has remained stable since the first AGAR inpatient survey in 2005 yet during the same time frame resistance to many antimicrobials, in particular tetracycline, trimethoprim-sulphamethoxazole and gentamicin, has significantly decreased. This suggests that non-multi-resistant community-associated MRSA (CA-MRSA) clones are becoming more common in the hospital setting and replacing the long-established multi-resistant clones such as ST239-III (Aus 2/3 EMRSA). Given hospital outbreaks of CA-MRSA are thought to be extremely rare it is most likely that patients colonised at admission with CA-MRSA have become infected with the colonising strain during their hospital stay.